2016
DOI: 10.7897/2277-4343.074172
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Pharmacognostic Study of Catharnthus Roseus Using Deep Eutectic Solvents

Abstract: Medicinal plant derived compound have an important role in the development of many clinically useful agents. Catharanthus roseus is a significant medicinal plant of the Apocynaceae family. Catharanthus roseus plant is used for different disease treatment such as skin cancer, Hodgkin's disease, breast cancer, and lymphoblastic leukemia. The aim of this study is conferring the comparative abundances of different phytochemicals, physiochemical and fluorescence analysis from Catharanthus roseus. Some of the chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
4
4
0
Order By: Relevance
“…The phytochemicals present in methanolic leaf extracts of the C. roseus plants had exposed the existence of seven phytochemicals for example alkaloids, carbohydrates, flavonoids, glycosides, phenols, steroids as well as tannins indicating that the rich presence of auxiliary metabolites. This is in understanding that of prior investigations by different workers [21,22,40,41,63]. Comparable phytoconstituents present in the raw extracts were recorded in the C. roseus with different plant parts like leaves by Govindasamy and Srinivasan [17] and Wagay et al [63], stem by Pham et al [49], flower by Govindasamy and Srinivasan [17], root by Govindasamy and Srinivasan [17], and stem bark by Rose and Priya [55].…”
Section: Characterization Of the Crplesupporting
confidence: 78%
“…The phytochemicals present in methanolic leaf extracts of the C. roseus plants had exposed the existence of seven phytochemicals for example alkaloids, carbohydrates, flavonoids, glycosides, phenols, steroids as well as tannins indicating that the rich presence of auxiliary metabolites. This is in understanding that of prior investigations by different workers [21,22,40,41,63]. Comparable phytoconstituents present in the raw extracts were recorded in the C. roseus with different plant parts like leaves by Govindasamy and Srinivasan [17] and Wagay et al [63], stem by Pham et al [49], flower by Govindasamy and Srinivasan [17], root by Govindasamy and Srinivasan [17], and stem bark by Rose and Priya [55].…”
Section: Characterization Of the Crplesupporting
confidence: 78%
“…The methanolic extract of C. roseus plant produces the typical light blue colour when seen under UV light (365 nm), and it was contrasted with colours oscillated from brown to green observed under visible light. This is in accordance with the previous discoveries of Nisar et al (2016aNisar et al ( , 2016b. It is very utilized in the biochemical investigation, for example, partition or seclusion of plant metabolites from the methanolic extracts of C. roseus plants.…”
Section: Characterization Of the Crplesupporting
confidence: 94%
“…The phytochemicals present in the methanolic leaf extracts of the C. roseus plants had exposed the existence of seven phytochemicals such as alkaloids, carbohydrates, avonoids, glycosides, phenols, steroids and tannins indicate that the rich presence of auxiliary metabolites. This is in understanding that of prior investigations by different workers (Wagay et al 2013;Kabesh et al 2015;Nisar et al 2016aNisar et al , 2016bKale et al 2018). Comparable phytoconstituents present in the raw extracts were recorded in the C. roseus with different plant parts like leaves by Govindasamy and Srinivasan (2012) and Wagay et al (2013), stem by Pham et al (2018), ower by Govindasamy and Srinivasan (2012), root by Govindasamy and Srinivasan (2012), and stem bark by Rose and Priya (2017).…”
Section: Characterization Of the Crplesupporting
confidence: 74%
See 1 more Smart Citation
“…However, it was found that there are little available information with regards to the polarity of DESs in the literature. In their studies, Nisar et al, [45] have used deep eutectic solvent composed of choline chloride and glycerol to extract some phytochemicals from Catharanthus roseus roots, stems, leaves, and flower petal. The results indicated the presence of many active chemical constituents including alkaloids, saponins, steroids, terpenoids, phenol, flavanoids and reducing sugar.…”
Section: Deep Eutectic Solvent As a Novel Benign Extractant For Bioacmentioning
confidence: 99%